2002
DOI: 10.2134/jeq2002.6900
|View full text |Cite
|
Sign up to set email alerts
|

Microcosm Wetlands for Wastewater Treatment with Different Hydraulic Loading Rates and Macrophytes

Abstract: Constructed wetlands (CW) usually require large land areas for treating wastewater. This study evaluated the feasibility of applying CW with less land requirement by operating a group of microcosm wetlands at a hydraulic retention time (HRT) of less than 4 d in southern Taiwan. An artificial wastewater, simulating municipal wastewater containing 200 mg L(-1) of chemical oxygen demand (COD), 20 mg L(-1) of NH4+-N (AN), and 20 mg L(-1) of PO4(3-)-P (OP), was the inflow source. Three emergent plants [reed, Phragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 10 publications
1
23
0
2
Order By: Relevance
“…Contaminant REs were estimated as the percentage change in concentration after treatment using Equation . Following this, relevant mass loading rate (MLR) and mass removal rate (MRR) in g*P/m 2 /day (P = pollutant concentration) for BOD 5 , TSS, NH 4 + ‐N, NO 3 − ‐N, and PO 4 3− as well as coliform unit removal in CFU/m 2 /day (CFU = colony forming units) for FC and TC were calculated using Equations and , respectively . RE =CiCoCi×100% MLR =Cnormali×HLR MRR = (CiCo)×HLR where, C i = Influent concentration of the wastewater parameter; and C o = Effluent concentration of the wastewater parameter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contaminant REs were estimated as the percentage change in concentration after treatment using Equation . Following this, relevant mass loading rate (MLR) and mass removal rate (MRR) in g*P/m 2 /day (P = pollutant concentration) for BOD 5 , TSS, NH 4 + ‐N, NO 3 − ‐N, and PO 4 3− as well as coliform unit removal in CFU/m 2 /day (CFU = colony forming units) for FC and TC were calculated using Equations and , respectively . RE =CiCoCi×100% MLR =Cnormali×HLR MRR = (CiCo)×HLR where, C i = Influent concentration of the wastewater parameter; and C o = Effluent concentration of the wastewater parameter.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been adopted for wastewater management in many parts of the world due to easy construction, low cost, simple operation, efficient and robust treatment , low sludge production , and superior ecological values . Many researchers have reported that CWs could remove a wide variety of pollutants effectively from wastewater including suspended solids, organic matter, nutrients, and heavy metals . Furthermore, it has been found that CWs can tolerate high variability of influent wastewater load .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Cross-sectional diagram of the constructed wetland system design. are often used to predict the breakdown of pesticides and nutrients as well as the removal of pathogenic microorganisms (Alvord and Kadlec, 1996;Jamieson et al, 2007;Jing et al, 2002;Kadlec, 1999;Khatiwada and Polprasert, 1999;Moore et al, 2001):…”
Section: Modeling Runoff Eventsmentioning
confidence: 99%
“…Several technologies for upgrading the quality of WSP effl uent have been studied (Harris et al, 1977;Middlebrooks, 1995;Saidam et al, 1995;Neder et al, 2002;Kim et al, 2003;Wang et al, 2005), among which intermittent sand fi lters (ISFs) and vertical fl ow constructed wetlands (VFCWs) have been successfully applied. Th e performance of these combined technologies is not completely understood because many variables, such as wastewater pretreatment, fi ltration media, planted macrophyte, hydraulic and organic loading rates, wastewater temperature, and dosing technique and frequency, aff ect the treatment effi ciency (Anderson et al, 1985;Jing et al, 2002).To increase the knowledge on the variables aff ecting the effi ciency of these treatment systems, a wastewater treatment plant (WWTP) combining WSP and ISF, and WSP and VFCW was built in the small community (300 population equivalents [PE]) of Aurignac, France. Th e experts participating in this project defi ned a protocol to collect data and knowledge from a 2-yr experimental operation of the Aurignac WWTP (Torrens et al, 2006).…”
mentioning
confidence: 99%